Industry and Country Effects on Managers' Perceptions of Environmental Uncertainties - Miller, Kent D. (Journal of International Business Studies, 1993)
International management research highlights political, government policy, and macroeconomic uncertainties. Strategy studies focus on input supply, product market, and competitive uncertainties. This study develops and tests the reliability of an instrument for measuring managers' uncertainly perceptions. Data analyses using an international sample provide insights into the relative importance of country and industry factors for explaining managers' perceptions of different environmental uncertainties.